Examining Avoidance, Victimization Risk, and Perceptions of Community Safety in Latinx Communities. (March 2023) - Yohros, Alexis; Geisler, Isabel; Lockwood, Sarah; Miller, Emelyn; Wills, Candence; Farrell, Amy; Cuevas, Carlos
Latinx adults are increasingly avoiding formal authorities, local services, and community engagement out of fear of victimization and deportation. Increased distrust and fear of authorities threaten to erode individual and community feelings of safety. While crime prevention scholarship identifies community efficacy, local engagement, and bonds to formal institutions as critical components to creating safety within local communities, there is little research to date on how avoidance in response to victimization impacts these processes. This study utilized data from 53 qualitative interviews of Latinx adults to understand the ways that bias victimization and discrimination alter feelings of community safety. Participants expressed distrust of formal institutions and decreased community engagement. They also leveraged informal networks like friends and family, emphasizing the nuanced impact of avoidance on community organization.